Computer Modeling of the LED Lighter with Fokonny Optics for a Video Projector - K. K. Gudinov; S. A. Dvurechensky; S. V. Kuklin; G. V. Tihomirova (Известия высших учебных заведений России: Радиоэлектроника)
Computer modeling and research of various variants of construction of light-diode illuminators for single-matrix LCD-video projector using inconsistent optical components are performed. The use of such components enables to form a light beam with the necessary parameters to align with the subsequent optical system. Computer modeling has allowed presents the analysis and evaluate the performance of the system developed in the design phase, and in some cases, and optimize it.